(untitled) (Research, Society and Development, 2022)
The transsexualizing process was implemented by the SUS in 2008 and expanded in 2013, with the main objective of providing comprehensive health care to the trans population, a population that does not find social recognition for its gendered experiences. The main objective of the present work is to discuss the experience of a multidisciplinary team in caring for trans people from the practices established in the transsexualizing ambulatory of a teaching clinic at the Federal University of Sergipe. This is an experience report of five professional categories: speech therapy, occupational therapy, nutrition, pharmacy and psychology, in the construction of practices that respond to the demands placed by this population in the daily life of a health service.